The Scope and Implications of Morals Not Knowledge - Evans, John Hyde (Zygon, 2019)
I greatly appreciate the opportunity provided by the editor of Zygon to further develop the ideas in my book Morals Not Knowledge: Recasting the Contemporary U.S. Conflict between Religion and Science in conversation with four critical commentaries. It is an honor to have one's work focused upon so intently, and I greatly appreciate the time and effort of the critics. The book was quite intentionally written as a provocation, an attempt at agenda setting, and as a call for changing the thinking of the entire religion and science academic community. In my previous writings I have kept close to the data, allowing myself at best mid-level conclusions, but this book is a foray into the abstraction and inevitable lack of precision required for high-level generalization. I hope that it continues to be generative of debate.